2019
DOI: 10.7150/jca.30818
|View full text |Cite
|
Sign up to set email alerts
|

MUS81 Inhibition Increases the Sensitivity to Therapy Effect in Epithelial Ovarian Cancer via Regulating CyclinB Pathway

Abstract: MUS81 is a key endonuclease involved in homologous recombination (HR) repair after DNA double-strand damage. Structure-specific endonucleases (SSEs) plays a crucial role in DNA replication, repair and transcription, and SSEs are also important for maintaining the secondary structure of DNA; therefore, their activity must be precisely controlled to ensure genome stability. We previously described that MUS81 expression was significantly correlated with CyclinB expression based on protein microarray analysis. Cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…In addition, a further investigation into the role of MUS81 in cellular response to anticancer treatment revealed that MUS81 lentivirus siRNA mediated knockdown in the colon cancer cell lines HCT116 and LS180 resulted in elevated cellular sensitivity to therapeutic drugs including cisplatin. This sensitisation was again mediated via the CHK1 signalling pathway followed by an S phase cell cycle arrest and an increase in cellular apoptosis [22][23][24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a further investigation into the role of MUS81 in cellular response to anticancer treatment revealed that MUS81 lentivirus siRNA mediated knockdown in the colon cancer cell lines HCT116 and LS180 resulted in elevated cellular sensitivity to therapeutic drugs including cisplatin. This sensitisation was again mediated via the CHK1 signalling pathway followed by an S phase cell cycle arrest and an increase in cellular apoptosis [22][23][24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms in MLH1 have also been associated with male infertility [178]. In addition, some of these DNA-remodeling enzymes, such as for example MUS81, are also emerging as potential targets in chemotherapeutic intervention [179][180][181][182]. Thus, advances in yeast studies have important implications in understanding the basis of human disorders linked to genome instability.…”
Section: Discussionmentioning
confidence: 99%
“…To circumvent resistance, therapies that include PARPi as an adjuvant to conventional chemotherapies have been tested and have sometimes cast promising results [ 129 , 137 ]. PARPi have also been combined with inhibitors for cell cycle checkpoint kinases such as ATR, CHK1, and WEE1 [ 138 , 139 ]; MUS81 nuclease inhibitors [ 140 ]; or signaling molecule inhibitors such as PI3K, AKT, or mTOR [ 141 ]. Inhibitors of alternative end-joining (Alt-EJ) polymerase theta are also under development as that appears to be the predominant repair choice for one-ended DSBs in HR-deficient cells [ 142 ].…”
Section: Cin and Cancer Therapiesmentioning
confidence: 99%